Association between unmet social needs and healthy lifestyle parenting behaviors - Kelsey A. Egan; Man Luo; Meghan Perkins; Ines Castro; Megan Sandel; Caroline J. Kistin; Elsie M. Taveras; Elsie M. Taveras; Lauren Fiechtner; Lauren Fiechtner; Lauren Fiechtner (Frontiers Media S.A., 2023)
ObjectiveTo examine cross-sectional associations of food and housing security risks and healthy lifestyle parenting behaviors related to nutrition and physical activity among families with children with overweight/obesity.MethodsWe surveyed 407 parents of children ages 6-12 years with overweight/obesity. Exposures were measures of food and housing insecurity risk. Outcomes were healthy lifestyle parenting behaviors related to nutrition and physical activity. Logistic regression models for each exposure-outcome relationship were adjusted for parental educational attainment, parental cohabitation status, household size, and household income.ResultsIn multivariable-adjusted models, food insecurity was associated with significantly lower odds of parent modeling exercise {aOR 0.60 [95% confidence interval (CI): 0.37, 0.96]} and parent modeling eating healthy foods [aOR 0.42 (95% CI: 0.24, 0.73)]. Housing insecurity was associated with significantly lower odds of parent modeling exercise [aOR 0.57 (95% CI: 0.35, 0.95)].ConclusionsFood insecurity and housing insecurity may be barriers to parents adopting and modeling healthy lifestyle parenting behaviors related to physical activity and nutrition.